2018
DOI: 10.1002/pen.24909
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal crystallization kinetics of poly(butylene terephthalate)/epoxidized ethylene propylene diene rubber/glass fiber composites

Abstract: Nonisothermal crystallization kinetics of poly(butylene terephthalate) (PBT)/glass fiber (GF) and PBT/epoxidized ethylene propylene diene rubber (eEPDM)/GF composites were investigated by differential scanning calorimetry (DSC) at a cooling rates of 2.5, 5, 10, and 20 °C/min, respectively. Morphologies of samples were observed with scanning electron microscopy and polarized optical microscopy. The specimens were prepared by melt blending. Analyses of the melt crystallization data by various macrokinetic models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…The Avrami model modified by Jeziorny is used to analyze the nonisothermal crystallization. [ 44 ] The Avrami equation modified by Jeziorny is Equation (5). 1goodbreak−Xtgoodbreak=exp()goodbreak−Zttn where n is the Avrami index, Z t is the kinetic crystallization rate constant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Avrami model modified by Jeziorny is used to analyze the nonisothermal crystallization. [ 44 ] The Avrami equation modified by Jeziorny is Equation (5). 1goodbreak−Xtgoodbreak=exp()goodbreak−Zttn where n is the Avrami index, Z t is the kinetic crystallization rate constant.…”
Section: Resultsmentioning
confidence: 99%
“…The Avrami model modified by Jeziorny is used to analyze the nonisothermal crystallization. [44] The Avrami equation modified by Jeziorny is Equation (5).…”
Section: The Avrami Analysis Of Nonisothermal Crystallizationmentioning
confidence: 99%
“…Or lg[]ln()1Xt=lgZt+nlgt where X t is the relative crystallinity; n is the Avrami index, which is related to nucleation, crystal growth, and crystal morphology; t is the time; and Z t is the total crystallization rate constant. Considering the non‐isothermal characteristics of the studied process, Jeziorny suggested that the crystallization rate parameter Z t can be corrected for the influence of cooling rate as follows [ 25 ] : lgZc=lgZt/φ where, Z c is the modified crystallization rate constant. Figure 11A–D present the plots of lg[−ln (1 − X t )] versus lg t .…”
Section: Resultsmentioning
confidence: 99%
“…However, PBT products suffer from brittle fracture and have low impact strength. [5,6] Hence, a blend obtained by combining ABS and PBT has the advantages of both; thus, ABS/PBT blends with desired performance such as high strength, excellent impact strength and good thermal stability can be obtained. [7,8] However, the ABS and PBT resins are immiscible owing to different solubility parameters and the crystallization of PBT.…”
mentioning
confidence: 99%
“…In general, compatibilizers used for the ABS/PBT blend are thermodynamically miscible with the ABS resin and contain epoxy or anhydride groups for the chemical reaction with PBT. [6,8,[11][12][13][14][15][16][17][18][19][20][21][22] Basu et al [15] used styrene maleic anhydride (SMA) as a compatibilizer for the PBT/ABS blend and reported that 5% SMA was optimal for the compatibilization of the PBT/ABS blend (70/30). Yao et al [16] reported that the addition of epoxy resin and styrene acrylonitrile maleic anhydride copolymer into the PBT/ABS blend induced a more stable molten phase structure, which was most suitable for the compatibilization of the blend.…”
mentioning
confidence: 99%